PERAN PENDIDIKAN KEWIRAUSAHAAN UNTUK MENGATASI KEMISKINAN - KHABIB ALIA AKHMAD (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2021)
Each country will face a variety of social problems, as well as the State of Indonesia which still faces the problem of poverty, even though the government has issued various policies. Possible one way that can be used to overcome social problems that occur in the community is the entrepreneurial approach in the form of the application of entrepreneurship education. The purpose of this study is to provide an overview of the role of entrepreneurship education factors in solving poverty problems. This study uses a qualitative approach, the research method used is literature exploration. From the results of the study found that the cause of poverty is the lack of education they have. On the other hand education makes individuals have the capacity or competence. Entrepreneurship education is able to provide knowledge and ability to someone to entrepreneurship as well as being a means or tool for creating human resources who have the ability to develop economic and welfare systems. So entrepreneurship education can be one way to reduce the amount of poverty in a country.